Multivitamin use and risk of preeclampsia: A systematic review and meta‐analysis. (7th April 2022) - Christiansen, Cecilie Holm; Høgh, Stinne; Rode, Line; Schroll, Jeppe Bennekou; Hegaard, Hanne Kristine; Wolf, Hanne Trap
Abstract: Introduction: Preeclampsia is associated with adverse maternal and neonatal outcomes. It is unclear whether multivitamin use reduces the risk of preeclampsia. This systematic review and meta‐analysis aimed to evaluate the association between multivitamin use and the risk of preeclampsia. Material and methods: We searched PubMed, Embase and the Cochrane Library from database inception to July 2021. Randomized controlled trials (RCTs), case–control and cohort studies assessing the association between multivitamin use and risk of preeclampsia were eligible. Studies of treatment with a single micronutrient were excluded. Relative risks and 95% confidence intervals (95% CI) were calculated using random‐effects models. RoB2, the Newcastle Ottawa Scale and GRADE were used to assess risk of bias and quality of evidence. The protocol was registered in PROSPERO (no. CRD42021214153). Results: Six studies were included (33 356 women). Only two RCTs were found, both showing a significantly decreased risk of preeclampsia in multivitamin users. These studies were not compatible for meta‐analysis due to clinical heterogeneity. A meta‐analysis of observational studies using a random‐effects model showed an unchanged risk of preeclampsia following multivitamin use (relative risk 0.85, 95% CI 0.69–1.03). The quality of evidence according to GRADE was very low. Conclusions: Very weak evidence suggests that multivitamin use might reduce the risk of preeclampsia; however, more research is needed. Large RCTs should be prioritized. The results of this review do not allow any final conclusions to be drawn regarding a preventive effect of multivitamin use in relation to preeclampsia.